TI_GERICHTE 15.2007.97 vom 14. Februar 2008 , Opposizione a precetto esecutivo. Ricorso contro la comminatoria di fallimento - TI Tribunale d'appello (2008)
Opposizione a precetto esecutivo. Ricorso contro la comminatoria di fallimento